Nutrition-related problems, nutritional support practices and barriers to adherence to nutritional guidelines during intensive treatment for acute myeloid leukemia: Patients' and hematology nurses' perspectives and experiences. (April 2022) - van Lieshout, Rianne; Lize, Nora; Tick, Lidwine W.; van Deursen, Judith; Driessen, Eline; Janssen, Tina; Custers, Stephanie; Kranenburg, Suzanne; van der Lee, Debbie; Koene, Harry R.; Beckers, Erik A.M.; Schouten, Harry C.; et al.
Summary: Background & aims: The updated guidelines of the European Society for Clinical Nutrition and Metabolism (ESPEN) and for Blood and Marrow Transplantation (EBMT) on nutrition in intensively treated acute myeloid leukemia (AML) patients recommend enteral nutrition (EN) instead of parenteral nutrition (PN) as the first-choice medical nutrition therapy. Despite this, PN remains the preferred route of nutrition administration in daily practice. The aim of this qualitative study was to gain insight into the patients' and hematology nurses' experiences and perceptions regarding nutritional problems and nutritional support and the reasons for the low adherence to the ESPEN/EBMT guidelines. Methods: Semi-structured interviews were conducted in 23 patients from various Dutch hospitals who had completed intensive AML treatment. Interviews with 22 patients were audio-recorded and transcribed, one interview was summarized. The transcripts and summary were thematically analyzed using Atlas.ti. From each of the 22 Dutch hospitals providing intensive AML treatment, one hematology nurse participated in a telephone questionnaire survey. The results of this survey are presented in a descriptive way. Results: Nutritional problems were a major source of distress in most participating patients. Nutritional support often led to peace of mind and less concerns, provided that there were no conflicting nutritional support practices among treating hospitals. Patients perceived PN and EN as a life-line and necessary for the prevention of or recovery from physical decline, but they also experienced loss of independence, limited mobility, fear of unwanted body weight gain and problems related to the feeding equipment. Both patients and hematology nurses regarded PN as an easy method of nutrition administration, while EN was often seen as a necessary evil or was even refused by patients, owing to tube-related physical discomfort and EN intolerance. Both patients' and hematology nurses' reluctance to administer EN proved to be barriers to the ESPEN/EBMT nutritional guideline adherence. Among the surveyed hematology nurses, barriers to adherence included personal factors related to their knowledge (lack of awareness) and attitudes (negative outcome expectancy and lack of agreement), guideline-related factors (lack of evidence) and external factors (lack of collaboration). Conclusion: Individualized nutritional support, including EN and PN, may reduce nutrition-related distress in intensively treated AML patients, provided that conflicting nutritional support practices among hospitals are avoided or explained. The barriers to adherence to the ESPEN/EBMT guidelines on EN and PN in this patient group may be reduced by enhancing hematology nurses' awareness and knowledge of the guidelines, incorporating the guidelines into multidisciplinary clinical pathways, improving outcome of EN by proper triage of patients eligible for EN and increasing the level of evidence of the guidelines.